Prevalence of Asthma and COPD and Blood Eosinophil Count in a Middle-Aged Belgian Population - Wijnant, Sara R. A. (J Clin Med, 2019)
Various phenotypes exist in asthma and Chronic Obstructive Pulmonary Disease (COPD). These are important to identify in order to guide treatment decisions. We aim to investigate the prevalence and clinical characteristics of obstructive airway diseases in the middle-aged population. We estimated the prevalence of COPD and/or asthma in the Asklepios cohort study (Belgium), using information from the third European Community Respiratory Health Survey (ECRHS3), medical records, and spirometry. Respiratory symptoms, respiratory medication, and current disease status distinguished clinical from sub-clinical cases. In addition, we compared the blood eosinophil count/µL (median [IQR]) between cases and controls. Of the 2221 participants (mean age 56.1 ± 5.9 years; 48.7% males), 138 (6.2%) participants had clinical current asthma, 22 (1.0%) participants had sub-clinical ever asthma, 102 (4.6%) had sub-clinical spirometry-defined COPD, 104 (4.6%) participants had clinical spirometry-confirmed COPD, and 11 (0.5%) had asthma and COPD overlap (ACO). Clinical current asthma (160.0 [110.0–250.0]), sub-clinical ever asthma (170.0 [110.0–230.0]), and clinical COPD (160.0 [110.0–220.0])—but less sub-clinical COPD (140.0 [90.0–210.0])—had higher eosinophil counts, compared to controls (130.0 [80.0–200.0]). We conclude that obstructive airway diseases are prevalent in the middle-aged Asklepios cohort. Moreover, the systemic eosinophil count is increased in clinical COPD cases, and in asthma cases regardless of clinical remission.